Preparation and characterization of wood/ceramic nanocomposites and their potential wood protection applications - Elmyra Husna, Hassanul Azhar (Universiti Malaysia Sarawak (UNIMAS), 2008)
This research focused on the preparation and characterization of wood/ceramic nanocomposites using metal oxide sols and selected wood samples. The metal oxide sols were prepared by the sol-gel technique. Wood/ceramic nanocomposites were prepared by submerging wood samples into the metal oxide sols under controlled conditions. Besides, the effectiveness of metal oxide nanoparticles for wood preservation was also being studied. Established characterization techniques using instruments such as Fourier Transformed Infrared Spectrometer (FTIR), Scanning Electron Microscopy (SEM), Optical Microscope and CHN Analyzer were used to characterize the wood/ceramic nanocomposites prepared under various conditions. Visual rating scale for decay and termites’ attacks were used to evaluate the effectiveness of selected metal oxides nanoparticles for wood preservation study.